2021
DOI: 10.3390/ijerph18158099
|View full text |Cite
|
Sign up to set email alerts
|

Barriers, Enablers, and Perceptions on Dietary Salt Reduction in the Out-of-Home Sectors: A Scoping Review

Abstract: In this review, we have investigated the perceptions, barriers, and enabling factors that were responsible for a dietary salt reduction in the out-of-home sectors. For this purpose, we examined different knowledge databases such as Google Scholar, Ebscohost, MEDLINE (PubMed), Ovid, and Cochrane Library for research articles from September to December 2020. The inclusion criteria for the research articles were that they had to be published in English and had to be a qualitative or quantitative study that was co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 86 publications
3
13
0
Order By: Relevance
“…The starting point may be involving reporters in salt reduction program to increase media coverage to increase public knowledge and healthy behaviors related to salt and health [30]. Evidence showed that although use of media is an important strategy to implement the NMSAP priority actions including food labeling, it may be insufficient to create change in the absence of other strategies to create an enabling environment based on increases in knowledge, but not necessarily behaviors, through mass media campaigns [31]. Other important facilitators noted by participants for the implementation of the NSMAP priority actions include favorable existing advertising strategies on smoking, public interest in health issues, and existence of school feeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…The starting point may be involving reporters in salt reduction program to increase media coverage to increase public knowledge and healthy behaviors related to salt and health [30]. Evidence showed that although use of media is an important strategy to implement the NMSAP priority actions including food labeling, it may be insufficient to create change in the absence of other strategies to create an enabling environment based on increases in knowledge, but not necessarily behaviors, through mass media campaigns [31]. Other important facilitators noted by participants for the implementation of the NSMAP priority actions include favorable existing advertising strategies on smoking, public interest in health issues, and existence of school feeding programs.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has not resulted in reported sales losses, product substitutions or increased table-side salt usage (41)(42)(43) . Adopting this strategy to prepare out-ofhome foods could involve gradually incorporating alternative ingredients such as herbs and spices and salt substitutes (27) .…”
Section: Discussionmentioning
confidence: 99%
“…Notably, these initiatives have yet to target the informal sector, specifically street food vendors. Nevertheless, several studies ( 27 ) , a case study-based framework ( 28 ) and an informative toolkit ( 29 ) have collectively provided insights into the existing challenges associated with salt reduction in this sector and enablers or suggestions to overcome them. In this qualitative study, the researchers identified specific barriers and enablers related to reducing salt content in foods within this sector, as perceived by Malaysian consumers and food operators.…”
Section: Discussionmentioning
confidence: 99%
“…This study aimed to determine the perceptions, barriers and enablers of salt reduction in the out-of-home sectors among the policy-makers, nongovernmental organizations (NGOs) and researchers, as well as the food industry. This study is part of a larger study on "Developing a policy to reduce the salt content of food consumed outside the home in Malaysia, " involving all formal and informal sectors [14,15].…”
Section: Introductionmentioning
confidence: 99%